Influence of Steam Curing Temperature on the Characteristic of Self-Compacting Concrete Incorporating Palm Shell Ash: Pengaruh Temperatur Perawatan Uap Terhadap Karakteristik Beton Memadat Mandiri dengan Abu Cangkang Sawit - Nurjannah, Siti Aisyah; Muliawan, Sutanto; Nurazizah, Ervi Tri Romayni; Asmarani, Dwi (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
Self-Compacting Concrete (SCC) is proven as durable concrete and applied to constructions. In this paper, a study was conducted to analyze the influence of variations of steam curing temperature (SCT) and water/binder (w/b) ratio on the characteristics of SCC incorporating 10% Palm Shell Ash (PSA) as a partial substitution for cement mass. The SCT was arranged from 25 C to 80 C. The variation of w/b in the compositions of SCC was 0.325, 0.350, and 0.375. The results showed that using PSA, the variation of SCT and the w/b ratio influenced the workability of the fresh concrete. The PSA, SCT, and the w/b ratio affected the concrete compressive strength and mass density. The increased SCT caused a lighter density and greater compressive strength. However, the decreased compressive strength occurred due to an excessive SCT of 70 C and above. The SCT of 60 C, 10% PSA, and w/b ratio of 0.350 in the mixture produced the greatest compressive strength of 36.27 MPa at 28 days of age, while without SCT, the greatest compressive strength of 36.78 MPa was achieved at the age of 28 days containing 10% PSA and w/b ratio of 0.325. It indicated that the w/b ratio was more influential than the SCT on the increase of the SCC compressive strength.